EP320 Laparoscopic radical hysterectomy versus open radical hysterectomy in early stage cervical cancer; long term recurrence rates in the south east wales gynaecology oncology centre. (1st November 2019) - Jones, S; Panda, A; Ramzan, I; Jones, R; Howells, R; Lim, K; Sharma, A
Abstract : Introduction/Background: Radical hysterectomy for cervical cancer may be performed using a minimally invasive approach or and open, abdominal surgical approach. A growing body of evidence provides conflicting evidence regarding survival outcomes between these two surgical approaches. This study contributes a retrospective review of 10 years of data from the South East Wales Gynaecology Oncology Centre. Methodology: A retrospective review of all cases of radical hysterectomy (open and laparoscopic) carried out between January 2008 and December 2018. Data collected included patient age, BMI, performance status, surgical approach, pre and post op cancer stage, tumour size, length of stay in hospital, complications, recurrence rates and disease free survival. Data were analysed using SPSS software, statistical significance was set at P≤0.05. Results: Two hundred and twenty-nine cases of radical hysterectomy were identified. One hundred and forty-one open, abdominal procedures and 88 minimally invasive procedures were carried out. Patient demographics and cancer stage were comparable between the two groups. Mean duration of follow up was 64 months. Nine out of 141 (6.4%) laparotomy cases developed a recurrence and 5/88 (5.7%) patients having had a laparoscopic procedure developed a recurrence. Conclusion: This retrospective review demonstrates no significant difference in recurrence rates between patients having undergone open, abdominal radical hysterectomy compared to minimally invasive hysterectomy in our centre. Disclosure: Nothing to disclose.